Errors In Writing Recount Text By The Seven Year Students Of SMP Negeri 3 Colomadu - Karmilasari, Karmilasari (2012)
This article represents the result of errors in writing recount text by the seven year students of SMP Negeri 3 Colomadu. The object of this research is focused on analyzing the erroneous writing of recount text made by the seven year students of SMP Negeri 3 Colomadu in 2011/2012 academic year. The objective of this research is to describe the errors made in the recount text written by the seven year students of SMP Negeri 3 Colomadu, especially (1) describes the types of errors, (2) describes the dominant of errors, and (3) identify the sources of errors. This research belongs to descriptive qualitative research. In collecting the data, the writer applies giving writing test to the students then documentation of students‟ essays. The writer analyzes thirty two students‟ worksheet. Their errors are then classified into groups after are indentified. Next, errors are analyzes by means of the theory of "linguistic category taxonomy' and "surface strategy taxonomy‟. The result of this research shows that; (1) There are 3 level errors; lexical error consists of The use of article with 18 errors or 12%, The use of preposition with 13 errors that equals 8,7%, The use of to be with 41 errors or 27,5%, The use of noun with 7 errors or 4,7%, The use of pronoun with 4 errors that equals 2,7%, The use of verb with 33 errors or 22,1%, The use of adverb with 2 errors or 1,3%, The use of modal with 4 errors or 2,1%, Inappropriate vocabulary with 1 error or 0,7%, Misspelled word with 2 errors or 1,3%, Word order with 2 errors or 1,3%. Syntactic level consist of The use of subject with 1 error or 0,7%, and The use of object with 1 error or 0,7%. Discourse level consists of 4 errors or 2,7% of generic structure, and 16 errors or 10,7% of language features, classified into 23 types of errors and it is derived from 15 types of errors. Based on the finding, it can be concluded that the students of SMP Negeri 3 Colomadu still make some errors in their recount text, and (2) the dominant error is The use of to be with 41 errors or 27,5%, it means that the students still have difficulties in this area, (3) There are two sources of errors; first is interlingual transfer, second is intralingual transfer.